Hypothermia vs Normothermia in Patients With Cardiac Arrest and Nonshockable Rhythm: A Meta-Analysis - Taccone, Fabio Silvio; Dankiewicz, Josef; Cariou, Alain; Lilja, Gisela; Asfar, Pierre; Belohlavek, Jan; Boulain, Thierry; Colin, Gwenhael; Cronberg, Tobias; Frat, Jean-Pierre; Friberg, Hans; Grejs, Anders M; et al. (JAMA neurology, 2024)
IMPORTANCE: International guidelines recommend body temperature control below 37.8 °C in unconscious patients with out-of-hospital cardiac arrest (OHCA); however, a target temperature of 33 °C might lead to better outcomes when the initial rhythm is nonshockable. OBJECTIVE: To assess whether hypothermia at 33 °C increases survival and improves function when compared with controlled normothermia in unconscious adults resuscitated from OHCA with initial nonshockable rhythm. DATA SOURCES: Individual patient data meta-analysis of 2 multicenter, randomized clinical trials (Targeted Normothermia after Out-of-Hospital Cardiac Arrest [TTM2; NCT02908308] and HYPERION [NCT01994772]) with blinded outcome assessors. Unconscious patients with OHCA and an initial nonshockable rhythm were eligible for the final analysis. STUDY SELECTION: The study cohorts had similar inclusion and exclusion criteria. Patients were randomized to hypothermia (target temperature 33 °C) or normothermia (target temperature 36.5 to 37.7 °C), according to different study protocols, for at least 24 hours. Additional analyses of mortality and unfavorable functional outcome were performed according to age, sex, initial rhythm, presence or absence of shock on admission, time to return of spontaneous circulation, lactate levels on admission, and the cardiac arrest hospital prognosis score. DATA EXTRACTION AND SYNTHESIS: Only patients who experienced OHCA and had a nonshockable rhythm with all causes of cardiac arrest were included. Variables from the 2 studies were available from the original data sets and pooled into a unique database and analyzed. Clinical outcomes were harmonized into a single file, which was checked for accuracy of numbers, distributions, and categories. The last day of follow-up from arrest was recorded for each patient. Adjustment for primary outcome and functional outcome was performed using age, gender, time to return of spontaneous circulation, and bystander cardiopulmonary resuscitation. MAIN OUTCOMES AND MEASURES: The primary outcome was mortality at 3 months; secondary outcomes included unfavorable functional outcome at 3 to 6 months, defined as a Cerebral Performance Category score of 3 to 5. RESULTS: A total of 912 patients were included, 490 from the TTM2 trial and 422 from the HYPERION trial. Of those, 442 had been assigned to hypothermia (48.4%; mean age, 65.5 years; 287 males [64.9%]) and 470 to normothermia (51.6%; mean age, 65.6 years; 327 males [69.6%]); 571 patients had a first monitored rhythm of asystole (62.6%) and 503 a presumed noncardiac cause of arrest (55.2%). At 3 months, 354 of 442 patients in the hypothermia group (80.1%) and 386 of 470 patients in the normothermia group (82.1%) had died (relative risk [RR] with hypothermia, 1.04; 95% CI, 0.89-1.20; P = .63). On the last day of follow-up, 386 of 429 in the hypothermia group (90.0%) and 413 of 463 in the normothermia group (89.2%) had an unfavorable functional outcome (RR with hypothermia, 0.99; 95% CI, 0.87-1.15; P = .97). The association of hypothermia with death and functional outcome was consistent across the prespecified subgroups. CONCLUSIONS AND RELEVANCE: In this individual patient data meta-analysis, including unconscious survivors from OHCA with an initial nonshockable rhythm, hypothermia at 33 °C did not significantly improve survival or functional outcome.
Keywords: senioři; terapeutická hypotermie; Prognosis; bezvědomí; Cardiopulmonary Resuscitation; mužské pohlaví; hypotermie; Adult; Hypothermia, Induced; kardiopulmonální resuscitace; Unconsciousness; prognóza; Humans; Out-of-Hospital Cardiac Arrest; dospělí; Hypothermia; zástava srdce mimo nemocnici; Aged; lidé; Male